CHRISTIANITY, SCIENCE, AND THREE PHASES OF BEING HUMAN: with Bruce R. Reichenbach, "Christianity, Science, and Three Phases of Being Human"; and Joona Auvinen, "On the Normative Significance of the Aims of Religious Practice.". - Reichenbach, Bruce R. (Zygon: Journal of Religion & Science, 2021)
The alleged conflict between religion and science most pointedly focuses on what it is to be human. Western philosophical thought regarding this has progressed through three broad stages: mind/body dualism, Neo‐Darwinism, and most recently strong artificial intelligence (AI). I trace these views with respect to their relation to Christian views of humans, suggesting that while the first two might be compatible with Christian thought, strong AI presents serious challenges to a Christian understanding of personhood, including our freedom to choose, moral choice itself, self‐consciousness, and the relevance of God to our beginning, being, and ending.